Stratified 3D Microtumors as Organotypic Testing Platforms for Screening Pancreatic Cancer Therapies. Issue 5 (10th February 2021) - Monteiro, Maria V.; Gaspar, Vítor M.; Mendes, Luís; Duarte, Iola F.; Mano, João F.
Abstract: Cancer‐associated pancreatic stellate cells installed in periacinar/periductal regions are master players in generating the characteristic biophysical shield found in pancreatic ductal adenocarcinoma (PDAC). Recreating this unique PDAC stromal architecture and its desmoplastic microenvironment in vitro is key to discover innovative treatments. However, this still remains highly challenging to realize. Herein, organotypic 3D microtumors that recapitulate PDAC‐stroma spatial bioarchitecture, as well as its biomolecular, metabolic, and desmoplastic signatures, are bioengineered. Such newly engineered platforms, termed stratified microenvironment spheroid models – STAMS – mimic the spatial stratification of cancer‐stromal cells, exhibit a reproducible morphology and sub‐millimeter size. In culture, 3D STAMS secrete the key molecular biomarkers found in human pancreatic cancer, namely TGF‐β, FGF‐2, IL‐1β, and MMP‐9, among others. This is accompanied by an extensive desmoplastic reaction where collagen and glycosaminoglycans (GAGs) de novo deposition is observed. These stratified models also recapitulate the resistance to various chemotherapeutics when compared to standard cancer–stroma random 3D models. Therapeutics resistance is further evidenced upon STAMS inclusion in a tumor extracellular matrix (ECM)‐mimetic hydrogel matrix, reinforcing the importance of mimicking PDAC‐stroma bioarchitectural features in vitro. The 3D STAMS technology represents a next generation of biomimetic testing platforms with improved potential for advancing high‐throughput screening and preclinical validation of innovative pancreatic cancer therapies. Abstract : Herein, a methodology to establish 3D stratified microenvironment spheroid models (STAMS) aiming to recapitulate the unique pancreatic ductal adenocarcinoma (PDAC) bioarchitecture is presented. Such an approach, enables the high‐throughput production of biomimetic PDAC models that recapitulate key tumor hallmarks including tumor microenvironment composition, the dynamic cancer‐stroma crosstalk, and resistance to anti‐cancer therapies. Therefore, being a promising platform for preclinical anti‐cancer drugs screening.